Therapeutic potential of berberine in attenuating cholestatic liver injury: insights from a PSC mouse model - Yanyan Wang; Derrick Zhao; Lianyong Su; Yun-Ling Tai; Grayson W. Way; Jing Zeng; Qianhua Yan; Ying Xu; Xuan Wang; Emily C. Gurley; Xi-Qiao Zhou; Jinze Liu; et al. (Cell & Bioscience, 2024)
Abstract Background and aims Primary sclerosing cholangitis (PSC) is a chronic liver disease characterized by progressive biliary inflammation and bile duct injury. Berberine (BBR) is a bioactive isoquinoline alkaloid found in various herbs and has multiple beneficial effects on metabolic and inflammatory diseases, including liver diseases. This study aimed to examine the therapeutic effect of BBR on cholestatic liver injury in a PSC mouse model (Mdr2−/− mice) and elucidate the underlying mechanisms. Methods Mdr2−/−mice (12–14 weeks old, both sexes) received either BBR (50 mg/kg) or control solution daily for eight weeks via oral gavage. Histological and serum biochemical analyses were used to assess fibrotic liver injury severity. Total RNAseq and pathway analyses were used to identify the potential signaling pathways modulated by BBR in the liver. The expression levels of key genes involved in regulating hepatic fibrosis, bile duct proliferation, inflammation, and bile acid metabolism were validated by qRT-PCR or Western blot analysis. The bile acid composition and levels in the serum, liver, small intestine, and feces and tissue distribution of BBR were measured by LC–MS/MS. Intestinal inflammation and injury were assessed by gene expression profiling and histological analysis. The impact on the gut microbiome was assessed using 16S rRNA gene sequencing. Results BBR treatment significantly ameliorated cholestatic liver injury, evidenced by decreased serum levels of AST, ALT, and ALP, and reduced bile duct proliferation and hepatic fibrosis, as shown by H&E, Picro-Sirius Red, and CK19 IHC staining. RNAseq and qRT-PCR analyses indicated a substantial inhibition of fibrotic and inflammatory gene expression. BBR also mitigated ER stress by downregulating Chop, Atf4 and Xbp-1 expression. In addition, BBR modulated bile acid metabolism by altering key gene expressions in the liver and small intestine, resulting in restored bile acid homeostasis characterized by reduced total bile acids in serum, liver, and small intestine and increased fecal excretion. Furthermore, BBR significantly improved intestinal barrier function and reduced bacterial translocation by modulating the gut microbiota. Conclusion BBR effectively attenuates cholestatic liver injury, suggesting its potential as a therapeutic agent for PSC and other cholestatic liver diseases.